The Effects of Local Administration of Aminophylline on Transureteral Lithotripsy - Ayyoub Barzegarnezhad; Abolfazl Firouzian; Seyed Abdollah Emadi; Nadali Mousanejad; Roksana Bakhshali (Advances in Urology)
Introduction. Urinary stone is a common cause of urinary tract disease. Stone excretion using ureteroscope is effective in inferior ureter. The aim of this study was to investigate the effects of aminophylline on ureteral spasm during ureteroscopy in acute phase of renal colic. Methods. In this double-blind randomized clinical trial, 120 patients with ureteral stones were enrolled and randomized into two groups. The bladder was drained and then received a 150 mL irrigation solution. Irrigation solution was saline and saline plus 10 mL aminophylline at 250 mg dose for control and case groups, respectively. Ureteroscopy and transureteral lithotripsy (TUL) were performed five minutes after irrigation. Results. The mean duration of TUL was 4.2±2.61 min and 8.4±2.9 min for control and case groups, respectively. The successful rate was 95% and 76.1% in case and control groups, respectively. Further extracorporeal shock wave lithotripsy (SWL) was performed in 5% and 30% for patients in case and control groups, respectively. Conclusion. Aminophylline facilitated ureteroscopy and increased the success rate in the treatment of renal colic using TUL. No significant complications from post-TUL were observed. Using aminophylline carries several advantages such as reducing procedure duration, decreasing the need for ureteral and double-J catheter, and reducing stone migration to the kidney and use of SWL.